Spirituality and psychological capital as predictors of psychological well-being in adults in Ecuador and Peru - López-Guerra, Víctor Manuel; Quinde, Dolores Lucia; Guevara-Mora, Sandra; Ocampo-Vásquez, Karina; Siguenza-Campoverde, Wilson Guillermo; de la Cruz, Cristina Díaz; Vivanco-Rios, Segundo Francisco; Rodríguez-Balcázar, Susan Cristy; Ramírez-Alva, José Melanio (Frontiers in Psychology, 2025)
BackgroundSeveral studies have indicated a positive association between positive psychological resources–such as spirituality and psychological capital–and psychological well-being. However, the specific nature of these relationships remains poorly understood.ObjectiveThe purpose of this study was to examine, through a model of structural equations, the influence of spirituality and psychological capital on psychological well-being, as well as to explore the relationship between these two predictor variables.MethodThe sample consisted of 1,044 adults living in Ecuador and Peru, aged between 18 and 71 years (M = 24; SD = 7.77), of whom 64.8% were women. The Ryff Psychological Well-being Scale (Ryff, 1989), the Parsian and Dunning Spirituality Scale (Parsian and Dunning, 2009), and a psychological capital questionnaire were used.ResultsStructural analyses showed a good fit of the proposed model according to the main goodness-of-fit indices. Psychological capital emerged as the most robust predictor of psychological well-being, explaining 13% of its variance, followed by spirituality. Likewise, a positive association was also evident between spirituality and psychological capital. Overall, the findings suggest that higher levels of these positive resources are related to greater psychological well-being.ConclusionThe results provide relevant empirical evidence on the promoting role of positive internal resources in psychological well-being, especially in Latin American contexts. The theoretical and practical implications are discussed, the study’s limitations are acknowledged, and future research is proposed.